PELATIHAN PEMBUATAN PUPUK KOMPOS SEBAGAI SOLUSI PERMASALAHAN SAMPAH DAUN KERING DI OBJEK WISATA “KALIANGET MANGUNAN” - Sejati, Gentur Ageng (WIKUACITYA: Jurnal Pengabdian Kepada Masyarakat, 2025)
Dry leaf litter is an environmental problem that is often ignored. The accumulation of dry leaves in the surrounding environment can cause various problems such as air pollution and disrupting the aesthetic value of a place. This research aims to identify the problem of dry leaves at the "kalianget Mangunan" tourist attraction and propose a solution in the form of counseling on making organic compost fertilizer to partners. The research method used is education and training. The results of the research carried out show that the "kalianget Mangunan" tourist attraction was successfully educated and agreed to adapt the method of managing dry leaf waste into compost organic fertilizer.